Laporan Kasus Epidemiologi Infeksi cVDPV2 Tahun 2023 di Jawa Barat, Indonesia: Surveilans dan Respons Wabah - Utoro, Sidik; Rachmadi, Dedi; Oktorina, Lenny; Feriandi, Yudi (Jurnal Biomedika dan Kesehatan, 2025)
Polio eradication remains a global health concern within the World Health Organization (WHO) framework, with Indonesia as a committed member. On February 21, 2023, an acute flaccid paralysis (AFP) case was diagnosed and reported in a 4-year-old girl from a village in Purwakarta District, West Java. The paralysis began on February 16, 2023. The child had no travel history and had never received any polio vaccination. Laboratory analysis of fecal specimens from the case and two nearby children indicated local transmission, confirming the presence of circulating vaccine-derived poliovirus type 2 (cVDPV2). This was Indonesia's first confirmed cVDPV2 outbreak. This article aims to provide a detailed description and analysis of the efforts made by relevant stakeholders in Indonesia to address this outbreak. According to WHO and national guidelines, two rounds of Sub-National Immunization Days (sub-NIDs) were carried out across all districts in West Java, the affected province. These sub-NIDs reached a total population of 3,984,797 with the novel oral poliovirus vaccine type 2 (nOPV2), achieving coverage of 96.2% in the first round and 92.3% in the second. An Outbreak Response Assessment (OBRA) was conducted in July 2023 by a team of ten international, multi-institutional assessors. The assessment concluded that, although the response was appropriate, it was too early to declare the outbreak over, as fewer than six months had passed since the last confirmed cVDPV2 detection. A follow-up review showed no new cases and no additional rounds of response immunization were recommended. This experience highlights the importance of strong surveillance, risk-based immunization planning, and community-focused communication in preventing future outbreaks. Program managers are advised to prioritize localized risk assessments, ensure even vaccine distribution, and remain prepared for rapid response.